Unusual antithyroid drug-induced hypoglycemia - Manish Gutch; Annesh Bhattacharya; Sukriti Kumar; Rajendra Kumar Pahan; Rao Somendra Singh (Wolters Kluwer Medknow Publications, 2017)
Insulin autoimmune syndrome is defined as the occurrence of spontaneous hypoglycemia attacks with high titers of anti-insulin autoantibodies in patients with no previous exposure to insulin. This rare syndrome has mostly been reported from the Japanese population and is frequently associated with other autoimmune conditions and certain drugs, especially those containing a sulfhydryl group. Most cases undergo spontaneous remission following removal of the offending drug. We hereby describe the case of a female who developed this rare syndrome following intake of carbimazole for Graves' disease.